A programme of absolute disorder decolonizing the museum - Vergès, Françoise 1952- (Pluto Press, 2024)
A call to end the Western museum
Keywords: Musée du Louvre; Entkolonialisierung; Museum; Westliche Welt; Museums / Curatorship / Moral and ethical aspects / History; Cultural appropriation / History; Museums and community / History; Decolonization; Postcolonialism; ART056000; ART059000; Abendländische Philosophie: Aufklärung; Archaeology; Archäologie; Colonialism & imperialism; Conservation, restoration & care of artworks; Dekolonisierung des Wissens / Dekolonialität; HISTORY / Social History; History of ideas; Kolonialismus und Imperialismus; Kunst: Erhaltung und Restauration; Museology & heritage studies; Museums- und Denkmalkunde; PHILOSOPHY / History & Surveys / Modern; POL045000; SOCIAL SCIENCE / Archaeology; Western philosophy: Enlightenment; Africa; Afrika